Myorelaxation in increase of efficiency of training process of athletes - Vysochin, Y. V.; Denisenko, Y. P.; Yatsenko, L.G. (International Journal of Sports Science, 2013)
At the present time a number of various ways of sportspersons' special physical capability based mainly on training and competitive loadings ramp up. They are effective enough to reach the main goal, but none of them provides sportspersons' health safety. Moreover, with the increase in volume and intensity of the loadings, which in sport have almost reached their limits, the sport traumatism and morbidity rate grow progressively. Proceeding from this, there was an evident necessity for the search of conceptually new ways for a simultaneous solution of these two the most complex and, in the opinion of many research workers, almost incompatible problems - the problem of achieving the highest levels of special physical working capacity, and the problem of sportspersons' health maintenance and improving -associated by us into one general problem of human motor activity efficiency enhancement. Therefore it is necessary to physiologically substantiated the basic methods and principles of special relaxation training, directed on increase of efficiency of process of training of sportsmen at all stages of the development of athletic skills. Under the efficiency of the motor activity, we understand achieve the highest levels of the special physical performance while maintaining sports longevity and health of athletes.